1983
DOI: 10.1093/oxfordjournals.eurheartj.a061531
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, coffee, tea and tobacco consumption: an epidemiological study in Algiers

Abstract: The connections and possible interactions between coffee consumption, tobacco consumption, blood pressure (BP), age, and body mass index (BMI) were analysed in a cross-sectional epidemiologic study of 1098 men and 393 women of the Algiers district. Systolic blood pressure (SBP) was negatively and significatively correlated with cigarette smoking. Diastolic blood pressure (DBP) was positively and significantly associated with coffee consumption (P less than 0.001) and negatively and significantly with cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
4

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
2
21
0
4
Order By: Relevance
“…In most studies, however, the effects of such important confounding factors were not considered thoroughly. In our review of the literature we have found studies that were adjusted for age and obesity, [7][8][9]12,13,19,[23][24][25][26] alcohol consumption, 14,24,25 physical activities 8,9,26 blood chemistry. 14,24,25 Most studies were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, however, the effects of such important confounding factors were not considered thoroughly. In our review of the literature we have found studies that were adjusted for age and obesity, [7][8][9]12,13,19,[23][24][25][26] alcohol consumption, 14,24,25 physical activities 8,9,26 blood chemistry. 14,24,25 Most studies were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups have reported that no association existed between smoking habit and blood pressure, [5][6][7][8][9] that blood pressure of smokers was lower than that of non-smokers, [10][11][12][13][14][15][16] or that smoking raised blood pressure. [17][18] In addition, a dose-effect relationship between daily smoking amount and blood pressure was significant in some studies, [13][14][15] while others failed to confirm this finding.…”
Section: Introductionmentioning
confidence: 99%
“…A few crosssectional studies have shown a positive association between habitual coffee consumption and blood pressure. [1][2][3][4][5] In the Busselton study, coffee consumption was directly related to blood pressure change over 6 years of follow-up. 11 In contrast to these reports, several observational studies have failed to identify a pressor effect of habitual coffee consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Some [1][2][3][4][5] but not all 6 -10 cross-sectional studies have identified a positive association between coffee drinking and blood pressure. At least one prospective study 11 has shown that coffee drinking is associated with an increase in blood pressure.…”
mentioning
confidence: 99%
“…Subsequently, numerous reports have found that smoking reduces blood pressure (Higgins and Kjelsberg 1967;Seltzer 1974;Berglund and Wilhelmsen 1975;Goldbourt and Medalie 1977;Gofin et al 1982;Agner 1983;Savdie et al 1984;Green et al 1986;Rosengren and Wilhelmsen 1987;Green et al 1991;Imamura et al 1996;Okubo et al 2002;Nagahama et al 2004;Okubo et al 2004;Wang et al 2006). In contrast, several other reports have found that smoking raises blood pressure (Elliott and Simpson 1980;Dyer et al 1982;Bolinder and de Faire 1998), while still others failed to confirm any effect on blood pressure (Arkwright et al 1982;Criqui et al 1982;Lang et al 1983;Simons et al 1984). Few large epidemiological studies on the effects of smoking on blood pressure have considered the confounding effects of such factors as age, obesity, blood chemistry, lifestyle or working conditions.…”
mentioning
confidence: 99%